Pengaruh Konsentrasi Jakaba Melalui Media Tanam dan Dosis Pupuk Npk Mutiara Terhadap Pertumbuhan dan Hasil Cabai Rawit (Capsicum frustescens L.) - Fiki, Mohamad; mawardi, mawadi (JURNAL AGROPLANT, 2025)
This study aims to determine the effect of NPK Mutiara and Jakaba fertilizers on the growth and yield of cayenne pepper plants (Capsicum frustescens). This study was conducted in Kemiri Songo Hamlet, Lampeji Village, Mumbulsari District, Jember Regency, East Java Province, starting from June 2024 to October 2024. This study was conducted using a 3 x 3 Randomized Block Design with 3 replications. The first factor is Jakaba consisting of three levels, namely: J0 = Without Jakaba, J1 = Jakaba 40 ml / L, J2 = Jakaba 80 ml / L. The second factor is NPK Mutiara fertilizer (P) consisting of 3 levels, namely: P1 = NPK Mutiara 2 g / polybag, P2 = NPK Mutiara 4 g / polybag, and P3 = NPK Mutiara 6 g / polybag. The data obtained were then analyzed by analysis of variance (ANOVA), if significantly different, it will be continued with the Duncan test with a level of 5%. The results showed that Jakaba concentrations of 40 ml/l (J1) and 80 ml/l (J2) did not have a significant effect on plant height, number of leaves, stem diameter and fruit weight per plant. Mutiara NPK fertilizer with a dose of 2 g/polybag had a significantly different effect on plant height and stem diameter. Treatment at a dose of NPK 4 g/polybag was significantly different in the number of leaves and fruit weight per plant.